Changes in Surface Electromyography during Physiotherapy as Influenced by Therapists' Length of Experience - Yumi Okayama; Shinichi Daikuya (International Journal of Physiotherapy)
Background: In Japan, the experience level of physiotherapists is often used to measure proficiency, regardless of other factors such as training quality. This approach cannot establish standards for quality and consistency among physiotherapists. This study aims to lay the foundation for standardizing education and evaluating employee performance in physiotherapy. Methods: The participants were 14 physiotherapists. Participants were tasked with performing specific physiotherapy skills related to weight-shifting, range of motion exercise, muscle strengthening exercise, and manual muscle testing. Electromyographic (EMG) activity in the participants' upper and lower extremities was measured while they performed the designated physiotherapy skills. Correlational statistical analysis was employed to determine whether therapists' length of experience affected EMG activity during these tasks. Results: The study found correlations between therapists' length of experience and EMG activity in specific muscles. The length of experience correlated strongly with brachioradialis activation in muscle strengthening exercises (MS-ex) of elbow flexion (r = 0.779), moderately with extensor carpi radialis in MS-ex of knee extension (r = 0.581), and manual muscle testing of hip abduction testing (r = 0.550), but negatively with gastrocnemius in range-of-motion exercises of hip flexion exercises (r = -0.670). Conclusion: Experienced therapists excelled at applying resistance optimally during trunk movements while stabilizing peripheral parts and maintaining effective positions, showing enhanced gastrocnemius muscle activity when required. These findings suggest that experience plays a significant role in the proficiency of physiotherapists and should be considered in efforts to standardize education and evaluate performance in the field.